PENERAPAN MODEL PEMBELAJARAN PROLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATERI PEMBAGIAN BILANGAN SATU ANGKA KELAS IV SD NEGERI BELLE II KABUPATEN TTS ( TIMOR TENGAH SELATAN) - Snae Mirna Salomi; Wara Sabon Dominikus; Nifu Benu Adam B (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Research Results by Mirna S. Snae Nim: 1901140340 (2026) PGSD. With the title Application of Problem Based Learning Model to Improve Student Learning Outcomes of Students of Division Material with Single Numbers Class 4 of Elementary School Belle II, the formulation of the problem is how the application of the Problem Based Learning model can improve student learning outcomes about division of single digit numbers at Elementary School Belle II, with the aim of knowing the application of the problem based learning (PBL) learning model can improve the activity and learning outcomes of fourth grade students of division material of single digit numbers at Elementary School Belle II, with the type of Classroom Action Research (PTK) with the following stages: planning, implementation, observation and reflection, with subjects of 24 students with details of 10 male students and 14 female students, with technical data collection through observation and tests. The results of the study showed that 9 students (37.5%) completed the first cycle of 24 students because they followed the lesson well and ended with being able to answer the test questions correctly. The teacher's weakness was because they were not able to provide good learning, while 15 students (62.5%) did not complete the first cycle because they liked to play and did not pay attention to the lesson properly. Furthermore, in the second cycle, the results of the study showed that 24 students (100%) completed the second cycle because they were able to follow all the learning activities well and were able to answer the questions given.